Toll-like receptor 3 in viral pathogenesis: friend or foe? - Perales-Linares, Renzo (Blackwell Science Inc, 2013)
Viral infections frequently induce acute and chronic inflammatory diseases, yet the contribution of the innate immune response to a detrimental host response remains poorly understood. In virus-infected cells, double-stranded RNA (dsRNA) is generated as an intermediate during viral replication. Cell necrosis (and the release of endogenous dsRNA) is a common event during both sterile and infectious inflammatory processes. The discovery of Toll-like receptor 3 (TLR3) as an interferon-inducing dsRNA sensor led to the assumption that TLR3 was the master sentinel against viral infections. This simplistic view has been challenged by the discovery of at least three members of the DExd/H-box helicase cytosolic sensors of dsRNA that share with TLR3 the Toll–interleukin-1 receptor (TIR) -adapter molecule TIR domain-containing adaptor protein interferon-β (TRIF) for downstream type I interferon signalling. Data are conflicting on the role of TLR3 in protective immunity against viruses in the mouse model. Varying susceptibility to infection and disease outcomes have been reported in TLR3-immunodeficient mice. Surprisingly, the susceptibility to develop herpes simplex virus-1 encephalitis in humans with inborn defects of the TLR3 pathway varies, and TLR3-deficient humans do not show increased susceptibility to other viral infections. Therefore, a current challenge is to understand the protective versus pathogenic contribution of TLR3 in viral infections. We review recent advances in the identification of TLR3-signalling pathways, endogenous and virus-induced negative regulators of the TLR3 cascade, and discuss the protective versus pathogenic role of TLR3 in viral pathogenesis.